2017
DOI: 10.1016/j.ajpath.2016.09.010
|View full text |Cite|
|
Sign up to set email alerts
|

Antiangiogenic Therapeutic Potential of Peptides Derived from the Molecular Motor KIF13B that Transports VEGFR2 to Plasmalemma in Endothelial Cells

Abstract: Vascular endothelial growth factor receptor 2 (VEGFR2) localized on the surface of endothelial cells (ECs) is a key determinant of the magnitude and duration of angiogenesis induced by vascular endothelial growth factor (VEGF). The kinesin family plus-end motor KIF13B transports VEGFR2 to the EC surface, and as such, specific inhibition of polarized VEGFR2 trafficking prevents angiogenesis. We designed a series of bioactive peptides based on deep analysis of VEGFR2-binding domain of KIF13B that compete specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…The VEGFR-2 kinase assay was performed to investigate whether isomangiferin is a potential VEGFR-2 inhibitor for breast cancer therapy. SU5408, the classical cell-permeable inhibitor of VEGFR-2 kinase, had an IC 50 of 72.42 nM, which was consistent with previous reports [ 22 ]. Isomangiferin also inhibited VEGFR-2 kinase activity with an IC 50 of 820.67 nM ( Supplementary Table 1 , available online).…”
Section: Resultssupporting
confidence: 92%
“…The VEGFR-2 kinase assay was performed to investigate whether isomangiferin is a potential VEGFR-2 inhibitor for breast cancer therapy. SU5408, the classical cell-permeable inhibitor of VEGFR-2 kinase, had an IC 50 of 72.42 nM, which was consistent with previous reports [ 22 ]. Isomangiferin also inhibited VEGFR-2 kinase activity with an IC 50 of 820.67 nM ( Supplementary Table 1 , available online).…”
Section: Resultssupporting
confidence: 92%
“…Our data also suggest a critical role for the motor protein KIF3A in this mechanism. Previous studies demonstrated that various motor proteins of the KIFs exhibit differential function to form intracellular cargo apparatus and regulate protein trafficking, including that of the vascular endothelial growth factor receptor 2 in endothelial cells (34), the glutamate receptor in the ventral nerve cord of Caenorhabditis elegans (worms) (35), and voltage-gated potassium (K v ) channels in mouse hippocampal neurons (36). Specifically, KIF3A mediates the polarized trafficking of K v 1.2 channel to axons (37,38) and the transport of vesicles containing -catenin toward the plasma membrane in the developing neuroepithelium (39).…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence has demonstrated that various subtypes of KIFs exhibit differential functions to form intracellular cargo apparatuses and regulate protein trafficking 13 . For example, upon binding with its target protein, KIF13B promotes the membrane translocation of vascular endothelial growth factor receptor 2 to the surface of endothelial cells 49 . Kinesin KIF13 also serves as a key regulator of anterograde glutamate receptor trafficking in the ventral nerve cord of Caenorhabditis elegans 50 .…”
Section: Discussionmentioning
confidence: 99%